2023
DOI: 10.7554/elife.81289
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic tumors exhibit myeloid-driven amino acid stress and upregulate arginine biosynthesis

Abstract: Nutrient stress in the tumor microenvironment requires cancer cells to adopt adaptive metabolic programs for survival and proliferation. Therefore, knowledge of microenvironmental nutrient levels and how cancer cells cope with such nutrition is critical to understand the metabolism underpinning cancer cell biology. Previously, we performed quantitative metabolomics of the interstitial fluid (the local perfusate) of murine pancreatic ductal adenocarcinoma (PDAC) tumors to comprehensively characterize nutrient a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Nevertheless, it is provocative to consider that general tissue homeostatic nutrient maintenance mechanisms are preserved in tumors, and that cancer cells may retain some dependence on nutrients defined by the adjacent origin tissue. To this end, it is notable that the metabolites found in RCC TIF differ from those reported in mouse pancreatic ductal adenocarcinoma (PDAC) TIF 14,49 , and from those found in interstitial fluid derived from mouse brain and mammary fat pad tissue 8 . Findings from analysis of PDAC TIF from tumors implanted in different tissue sites also noted differences in metabolite levels 14 , supporting the notion that cancer must adapt to a specific tissue nutrient environment rather than determine the majority of nutrients present.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, it is provocative to consider that general tissue homeostatic nutrient maintenance mechanisms are preserved in tumors, and that cancer cells may retain some dependence on nutrients defined by the adjacent origin tissue. To this end, it is notable that the metabolites found in RCC TIF differ from those reported in mouse pancreatic ductal adenocarcinoma (PDAC) TIF 14,49 , and from those found in interstitial fluid derived from mouse brain and mammary fat pad tissue 8 . Findings from analysis of PDAC TIF from tumors implanted in different tissue sites also noted differences in metabolite levels 14 , supporting the notion that cancer must adapt to a specific tissue nutrient environment rather than determine the majority of nutrients present.…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies have found that arginine is depleted to very low levels in murine pancreatic cancer TIF 14,49,50 , a phenomenon facilitated by myeloid-derived arginase activity 49 . Of note, arginine is not significantly depleted in KIF or TIF from RCC patients compared to plasma, although levels of related urea cycle metabolites are reduced in TIF and KIF compared to plasma (Figure 2E) .…”
Section: Resultsmentioning
confidence: 99%
“…Arginine is a non-essential or semi-essential amino acid involved in several biological functions such as cell proliferation, survival and protein synthesis, and it also acts as a precursor for the synthesis of molecules involved in tumorigenesis and tumor progression in PDAC, such as nitric oxide and polyamines, among others [ 57 , 58 ]. Arginine biosynthesis upregulation has been reported in pancreatic tumors [ 59 ]. Arginine metabolism facilitates PDAC progression, and its depletion has been associated with the suppression of cell invasion, migration and proliferation and the promotion of autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This consumption also has effects on tumor cells. A recent study showed that pancreatic tumors must upregulate arginine biosynthesis to compensate for this competition for local arginine ( 115 ).…”
Section: Arginine Metabolismmentioning
confidence: 99%